Prevention of Money Laundering Crimes through customer due diligence and enhanced due diligence in Savings and Loans Cooperatives (Study of Savings and Loans Cooperatives in Medan) - Sunarmi, Sunarmi; Marlina, Marlina; Sukarja, Detania; Hasibuan, Rahmat Anshar (Inspiring Law Journal, 2024)
Money Laundering Crimes are carried out by various Financial Services Companies. Article 17 of Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering states that the companies involved in TPPU, one of the service provider companies in Article 17 is a cooperative that carries out savings and loan activities. The problems in this research are how to regulate the prevention of money laundering crimes through savings and loan cooperatives, what is the accountability of savings and loan cooperatives involved in money laundering crimes, then how is the implementation of the principles of customer due diligence and enhanced due diligence in preventing and eradicating money laundering crimes in saving and loan cooperative. This research uses normative and empirical legal research methods. The research approach is a statutory approach or a juridical approach, the material in this thesis is taken from secondary data. The data collection techniques that the researcher carried out were interviews and literature studies. The results of the analysis and research in this thesis are to analyze and find out all the arrangements for preventing money laundering crimes through savings and loan cooperatives, to analyze the accountability of savings and loan cooperatives involved in money laundering crimes, so that they know and analyze the implementation of the principles of customer due diligence and enhanced due diligence. diligence in savings and loan cooperatives. Arrangements for TPPU Prevention through KSP through Article 18 of the PPTPPU Law, Article 13 POJK No 12/POJK.01/2017, regulations of the Minister of Cooperatives and Small and Medium Enterprises as regulated in Article 8 of the Minister of Cooperatives and SMEs Regulation, KSP responsibilities involved in TPPU will be given administrative sanctions, The punishment that can be used on cooperatives is the basic penalty and additional criminal penalties. Implementing the principles of customer due diligence and enhanced due diligence in KSP has been implemented in Savings and Loans Cooperatives by prioritizing assessments of customers who wish to apply for loans or deposit money